Exploring the factors contributing to the decline in the international student supply chain to UK universities in 2024 - Hunaiti, Ziad; Sultan Altamimi, Lubna (Journal of International Students, 2026)
International student numbers continue to rise, and the UK was historically among the top five English-speaking destinations. However, in 2024, it experienced a significant decline in international student enrollment, with Australia overtaking it in global rankings. This decline, contemporaneous with a spike in the UK’s anti-immigration political consensus, particularly owing to changes in student visa policies and restrictions on dependents, poses serious economic risks to UK universities, which rely heavily on international tuition fees, the local economies of university towns, and the UK’s long-term global reputation. This systematic mapping review explores causative factors from 32 published news articles categorized through the political, economic, social, technological, legal, and environmental (PESTLE) framework. The findings show that political, economic, social, and legal/regulatory issues—such as visa restrictions, increased costs, and stricter immigration rules—are key drivers. The results offer actionable insights and recommendations for UK policymakers and higher education institutions.